Memory and Literature: Colonization and Construction of the Past in the Novel Pachinko (2020)
Memory is the construction of the past and, directly linked to experience, it is related to social, cultural, or political identities. It enables ways of understanding disputes and consensus on the meaning attributed to the past. This paper analyzes various aspects of Korean history and culture during the Japanese colonial rule of 1910–1945, as depicted in “Pachinko” (2017), one of the first novels written for the Anglo-Saxon audience on this theme. It is addressed using an analysis based on memory and history, taking into account the experiences of the Korean people exiled in Japan.